Radiotherapy- and chemotherapy-induced normal tissue damage - Plevová, Pavlina (Radiology and oncology (Ljubljana), 2002)
Background. lonising radiation and cytostatic agents used in cancer therapy exert damaging effects on normal tissues and induce a complex response at the cellular and molecular levels. Cytokines and adhesion molecules are involved in this response. Methods. Published data on the given topic have been reviewed. Results and conclusions. Various cytokines and adhesion molecules, including tumor necrosis factor a, interleukins-1,-2,-4, and -6, interferon gamma, granulocyte macrophage- and macrophage- colony stimulating factors, transforming growth factor beta, platelet-derived growth factor, insulin-like growth factor 1, fibroblast and epidermal growth factors, platelet-activating factor, intercellular adhesion molecule-1, vascular cell adhesion molecule-1, E- and P-selectins are involved in the response of normal tissues to ionizing radiation- and chemotherapy-induced normal tissues damage and are co-responsible for some side effects of these treatment modalities, including fever, anorexia and fatigue, suppression of hematopoiesis, both acute and latelocal tissue response.
Keywords: Adverse effects; Antineoplastic agents; Antineoplastiki; Celična adhezija, molekule; Cell adhesion molecules; Citokini; Cytokines; Drug effects; kemoterapija; onkologija; poškodbe tkiva; Radiation effects; radioterapija; therapy; zdravljenje